Annealing-free efficient vacuum-deposited planar perovskite solar cells with evaporated fullerenes as electron-selective layers. (January 2016) - Zhao, Dewei; Ke, Weijun; Grice, Corey R.; Cimaroli, Alexander J.; Tan, Xinxuan; Yang, Mengjin; Collins, Robert W.; Zhang, Hongmei; Zhu, Kai; Yan, Yanfa
Abstract: We present efficient metal oxide-free and annealing-free planar perovskite solar cells with the regular cell structure using vacuum-deposited fullerenes C60 and C70 as the electron-selective layers and vacuum-processed perovskites as the light absorbers. The devices with an ultrathin C60 layer (5.5 nm) yielded an average power conversion efficiency of 14.3% and a maximum efficiency of 15.7%. The best-performing cell produced a steady-state efficiency of 14.6%. The high performance is attributed to the efficient blocking of holes and extraction of electrons by C60 due to a favorable energy level alignment between the C60 and the fluorine-doped tin oxide electrodes. With the realization of efficient cells, the annealing-free vacuum deposition of perovskite absorbers and C60 or C70 electron-selective layers and intermediate layers demonstrates its power for fabricating all-perovskite tandem solar cells. Graphical abstract: Highlights: Annealing-free vacuum-deposited regular perovskite solar cells with high efficiency of 15.7% were fabricated. Ultrathin thermally evaporated C60 and C70 work as the electron-selective layers, indicating efficient blocking of holes and extraction of electrons. This suggests vacuum-deposited fullerenes are promising candidates as the intermediate layer for fabricating all-perovskite tandem solar cells.